2010
DOI: 10.1007/s00482-010-0958-3
|View full text |Cite
|
Sign up to set email alerts
|

Chronische Schmerzen in deutschen Facharztpraxen

Abstract: Chronic pain is a major problem in primary care. The high level of suffering and the enormous socioeconomic impact on public health demand consequences. Improvements in undergraduate and postgraduate training are urgently required for both an adequate pain treatment and the prevention of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…There is no doubt that a link exists between visits to healthcare institutions and physical pain, which is consistent with previous research ( 32 ) that chronic pain increases the burden on public health services and has a significant socioeconomic impact. This study found that older adults with physical pain were 1.28 times more likely to visit a Western hospital than older adults without physical pain, and 1.42 times more likely to visit other healthcare providers.…”
Section: Discussionsupporting
confidence: 91%
“…There is no doubt that a link exists between visits to healthcare institutions and physical pain, which is consistent with previous research ( 32 ) that chronic pain increases the burden on public health services and has a significant socioeconomic impact. This study found that older adults with physical pain were 1.28 times more likely to visit a Western hospital than older adults without physical pain, and 1.42 times more likely to visit other healthcare providers.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic pain syndromes, especially chronic low back pain (CLBP) is one of the most prevalent diseases in Western populations [1] and is one of the most common reasons for primary care consultations [2]. CLBP is associated with a high burden of disease with respect to health care costs and patients’ quality of life [3].…”
Section: Introductionmentioning
confidence: 99%
“…Results of a German study that determined the prevalence of chronic pain in six different practices (general medicine, surgery, internal medicine, neurology, oncology and orthopaedics) showed that pain is the main reason to seek a doctor for 42.5% of patients. Forty percent of those patients suffer from chronic pain, affecting more women than men …”
Section: Introductionmentioning
confidence: 99%
“…Forty percent of those patients suffer from chronic pain, affecting more women than men. 1 Today, the established therapy of cancer pain as well as chronic non-cancer pain (CNCP) is based on a World Health Organization (WHO) guideline published in 1986, updated in 1996. [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%